PENGARUH PENERAPAN TEKNIK BISNIS BERISIKO TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN DURIAN TARUNG PADANG - Ramanda, Randi; Aima, Zulfitri; Pratiwi, Merina (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research was motivated by the students understanding of mathematical concepts was still low. This study aims to determine whether students understanding of mathematical concepts by applying Bisnis Berisiko Technique than students understanding of mathematical concepts with the application of conventional learning. This was an experimental research which used Pre-Experimental Design: Static Group Comparison. The population of the research was the students in class VIII of MTsN Durian Tarung Padang registered in academic year 2013/2014. The instrument of the research was a posttest. The data collected was analyzed by using software MINITAB. The result of the research showed that the average score of the students in the experimental group was 54,01 and in the control class was 28,44. The result of the t-test indicated that the hypothesis was accepted. Based on these results, it was concluded that the students understanding of mathematical concepts by applying Bisnis Berisiko Technique was better than the students understanding of mathematical concepts by applying conventional learning in class VIII of MTsN Durian Tarung Padang. Â